Pengembangan Modul Keanekaragaman Hayati Berbasis Pendekatan Saintifik Untuk Siswa Kelas X SMA/MA Sederajat - Siti Mardiana Kliyanti; Rodiantifitri Nengsih; Eni Yulianti (BIOCOLONY, 2018)
This research is motivated by the absence of teaching materials that can be used to assist in teaching and learning activities, especially about biodiversity material. In the teaching and learning process the teacher only uses worksheets that are less interesting and not pictorial so that they cannot help students to study independently. This study aims to produce a biodiversity module based on a scientific approach for students of class X SMA/MA equivalent. This type of research is a method of research and development using a 4-D model namely Define, Design, Develop and Disseminate. The subjects of this study were 4 validators and validators for practicality tests, namely 2 teachers and 20 students of class X MAN 2 Merangin. Data from this study are the results of the validity questionnaire and module practicality questionnaire, then this data is analyzed by descriptive analysis. Based on this research produced a product in the form of a Biodiversity Module Based on a valid and practical Scientific Approach. The module is declared to be very valid by the validator both in terms of content, linguistic, presentation and graphic aspects with a validity value of 92%. The modules produced are also practical by teachers and students both in terms of ease of use, learning time and attractiveness with an average value of 3.48 for teachers and for students 3.21. So that it can be concluded that the Scientific Biodiversity Based Module produced is declared valid and practical.